Effect of Red Andong Leaf Infusion (Cordyline fruticosa L. A. Cheval) on HbA1c Levels in Diabetic Mice (Mus musculus) - Adhinda Kayla Sahwa D.; I gede Andika Sukarya; Dwi Setiyo Prihandono (Afiyatun Journal of Health Sciences, 2026)
Background: Diabetes mellitus is a chronic metabolic disease characterized by hyperglycemia which can lead to serious complications. Hemoglobin A1c (HbA1c) is an important biomarker reflecting average blood glucose over 2–3 months. Red Andong leaves (Cordyline fruticosa L.A. Cheval) contain bioactive compounds — saponins, flavonoids, and tannins — with potential antidiabetic activity. Methods: This experimental study used a pretest-posttest control group design. Sixteen male mice induced with alloxan were randomly assigned to two groups: a control group (no treatment) and a treatment group receiving 1 mL of red Andong leaf infusion orally twice daily for 14 days. Data normality was assessed using the Shapiro-Wilk test, followed by a Paired T-Test for between-group comparison. Results: Mean HbA1c in the treatment group before intervention was 5.494% (min 4.4%, max 6.6%). After 14 days, HbA1c decreased to a mean of 5.075% (min 3.4%, max 6.3%). Paired T-Test yielded p = 0.00 (p < 0.05), indicating a statistically significant difference between pre- and post-intervention HbA1c levels. Conclusion: Red Andong leaf infusion significantly reduced HbA1c levels in diabetic mice. The effect is attributed to the combined action of flavonoids (enhancing glycogenesis and β-cell regeneration), tannins (inhibiting α-glucosidase), and saponins (inhibiting intestinal glucose absorption).